The Psychological Pull of FoMO in Consumer Behavior: a Literature Review - Hartini Pratiwi Pane; Syahrika Luthfi; Ismail Napitupulu; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (International Journal of Economics and Management Sciences, 2024)
The purpose of the research is to find out FoMO in analyzing customer satisfaction. SLR method in writing this article, literature review plays an important role in formulating research ideas, understanding previous findings related to the topic raised, and identifying gaps in existing knowledge. A systematic literature review (SLR) was conducted in two well-known databases, ScienceDirect and Scopus. After applying inclusion and exclusion criteria, 1,098 out of 3,977 articles were deemed relevant. Thereafter, these papers were carefully examined to produce an in-depth analysis of the subject. Ultimately, 13 papers were selected for in-depth examination in this study. Based on data from SLR the articles were written between 2021 and 2024. The research methodology used in this paper includes descriptive analysis and bibliographic analysis. The results of writing the article found that Fear of Missing Out (FoMO), which capitalizes on the feeling of fear of missing an opportunity, is proven to increase consumer confidence to make a purchase immediately. Effective marketing strategies in leveraging Fear of Missing Out (FoMO) often involve elements of time constraints and product popularity that can trigger impulsive behavior in consumers. Social media marketing also plays an important role by creating interactions that attract consumers through trending content. The findings in this study enable brands to strengthen emotional connections with consumers, expand reach, and drive engagement in purchase decisions.